ARUS KAS OPERASI, LEVERAGE, SALES GROWTH TERHADAP FINANCIAL DISTRESS - Melsa Aninda Fitri; Vaya Juliana Dillak (JRAK, 2020)
The purpose of this study is to determine how the influence of operating cash flow, leverage and sales growth ratios on the occurrence of financial distress. The research method used in this study is a quantitative method. While the data collection techniques used in this study are purposive sampling. The population in this study is the textile and garment subsector companies listed on the Indonesia Stock Exchange in 2015-2018 as many as 14 companies with observational data of 56 samples. This study uses panel data regression analysis techniques. Simultaneous variable operating cash flow, leverage, and sales growth have a significant effect on financial distress. And then, leverage has a significant effect on financial distress. While the operating cash flow and sales growth partially did not have significant effect on financial distress.